Abandoning Ankara: voluntary departures from the Grand National Assembly of Turkey. Issue 4 (2nd October 2019) - Yildirim, T. Murat; Overby, L. Marvin
ABSTRACT: Although retirements account for a significant percentage of turnover in a good many legislatures around the world, they have received little scholarly attention outside of legislative institutions of advanced democracies, particularly the United States Congress. In this paper, we address this shortcoming in the literature by exploring retirement dynamics in Turkey, a transitional democracy and an ideologically polarised political system. Using a unique dataset of parliamentarians who served in the Grand National Assembly of Turkey (GNAT) between 2007 and 2015, we show significantly higher rates of non-electoral departure among members of opposition parties and especially among those representing Kurdish regions of the country. We supplement this analysis in two ways to delve further into potential factors behind retirement decisions. First, we examine data on government answers to parliamentary questions in the period 2007–2015. Second, we analyse a survey of Turkish parliamentarians serving in the early 2000s regarding career plans. These data permit us to examine the roles of system inclusiveness and parliamentary socialisation on decisions not to stand for reelection. Our results imply that perceived legislative influence may help explain some of the variation in retirement decisions.